Implementation of the redesigned Community Health Fund in the Dodoma region of Tanzania: A qualitative study of views from rural communities. (8th January 2017) - Kalolo, Albino; Gautier, Lara; Radermacher, Ralf; Stoermer, Manfred; Jahn, Albrecht; Meshack, Menoris; De Allegri, Manuela
Summary: The need to understand how an intervention is received by the beneficiary community is well recognised and particularly neglected in the micro–health insurance (MHI) domain. This study explored the views and reactions of the beneficiary community of the redesigned Community Health Fund (CHF) implemented in the Dodoma region of Tanzania. We collected data from focus group discussions with 24 groups of villagers (CHF members and nonmembers) and in‐depth interviews with 12 key informants (enrolment officers and health care workers). The transcribed material was analysed thematically. We found that participants highly appreciate the scheme, but to be resolved are the challenges posed by the implementation strategies adopted. The responses of the community were nested within a complex pathway relating to their interaction with the implementation strategies and their ongoing reflections regarding the benefits of the scheme. Community reactions ranged from accepting to rejecting the scheme, demanding the right to receive benefit packages once enrolled, and dropping out of the scheme when it failed to meet their expectations. Reported drivers of the responses included intensity of CHF communication activities, management of enrolment procedures, delivery of benefit packages, critical features of the scheme, and contextual factors (health system and socio‐political context). This study highlights that scheme design and implementation strategies that address people's needs, voices, and values can improve uptake of MHI interventions. The study adds to the knowledge base on implementing MHI initiatives and could promote interests in assessing the response to interventions within the MHI domain and beyond.